Ungarn 1944-1945 - Fritz, Regina 1980- (De Gruyter Oldenbourg, 2021)
As military defeat loomed large, Nazi Germany occupied Hungary. Immediately, the Nazis began the deportation of Jews living under Hungarian rule. The volume documents the fate of over 700,000 persons, from the First Anti-Jewish Law in 1938 to the radicalization of persecution under German occupation
Keywords: Geschichte 1944-1945; Judenverfolgung; Quellen; Ungarn; jüdische Geschichte; HISTORY / Holocaust; Quelle